3D dynamic cultures of HGSOC organoids to model innovative and standard therapies - Cavarzerani, Enrico; Caligiuri, Isabella; Bartoletti, Michele; Canzonieri, Vincenzo; Rizzolio, Flavio (Frontiers in Bioengineering and Biotechnology, 2023)
High grade serous ovarian cancer (HGSOC) needs new technologies for improving cancer diagnosis and therapy. It is a fatal disease with a few options for the patients. In this context, dynamic culture systems coupling with patient derived cancer 3D microstructures could offer a new opportunity for exploring novel therapeutic approaches. Here, we optimized a passive microfluidic platform with 3D cancer organoids, which allows a standardized approach among different patients, minimum requirement of samples, multiple interrogations of biological events and a rapid response. The passive flow was optimized to improve the grow of cancer organoids avoiding the disruption of extracellular matrix (ECM). Under optimized conditions of the Organoflow (tilting angle of 15° and interval of rocking every 8’), the cancer organoids growth faster than static conditions and the number of dead cells is reduced over time. To calculate the IC50 values of standard chemotherapeutic drugs (carboplatin, paclitaxel and doxorubicin) and targeted drugs (ATRA) different approaches were utilized. Resazurin staining, ATP based assay and DAPI/PI colocalization assays were compared and the IC50 values calculated. The results showed that in the passive flow, the IC50 values are lower than static conditions. FITC-labeled paclitaxel shows a better penetration of ECM under passive flow than static conditions and cancer organoids start to die after 48 hours instead of 96 hours, respectively. Cancer organoids are the last frontiers for ex vivo testing of drugs that replicate the response of patients in clinic. For this study organoids derived from ascites or tissue of patients with Ovarian Cancer have been used. In conclusions, it was possible to develop a protocol for organoid cultures in a passive microfluidic platform with a higher growth rate, fast drug response and a better penetration of drugs into ECM, maintaining the samples vital and collecting the data on the same plate up to 16 drugs.